Stockpiling supplies for disaster response: an experimental analysis of prepositioning biases (2018)
Several relief organisations preposition supplies in preparation for disaster response. We show how the structure of prepositioning decisions resemble newsvendor decisions and how common newsvendor biases could affect prepositioning performance. To explore prepositioning biases, we run a behavioural experiment of a prepositioning problem with 20 practitioners from the humanitarian sector. Their task was to choose prepositioning quantities under different cost conditions and for supplies with different degrees of criticality. Results show that participants pull orders away from optimum (pull-to-centre) and follow the prior beneficiary demand realisation (demand chasing) regardless of cost and criticality conditions. However, the estimation of behavioural models reveals patterns hidden in averages, showing that participants weigh undersupply costs more for urgent supplies and urgency moderates demand chasing. A follow-up validation experiment manipulates the salience of urgent supplies by bundling them with non-urgent supplies in a portfolio. Results show that the portfolio strengthens these patterns, increasing the availability of urgent supplies. We offer practice implications of these findings for prepositioning activities and theory implications for inventory experiments in general. © 2019, © 2019 Informa UK Limited, trading as Taylor and Francis Group.